PENGARUH PEMAHAMAN KITAB MINHAJUS SALIKIN TERHADAP KUALITAS IBADAH SALAT SISWA DI PONDOK JAJAR ISLAMIC CENTER TAHUN AJARAN 2024/2025 - Vibisono, Herlambang Sofyan; Rochmawan, Alfian Eko; Syamsuddin, S (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This study aims to examine the effect of understanding the book of Minhajus Salikin on the quality of worship of students of the Jajar Islamic Center Islamic Boarding School in the 2024/2025 school year. The study used a quantitative approach with a questionnaire data collection method that had been tested for validity and reliability and a test involving 39 students as the study population. Data obtained through questionnaires, and analyzed using statistical tests with the help of SPSS. From the acquisition of the calculated value of tcount > ttable of 2.033> 1.687 and a significance value of 0.049 <0.05, the magnitude of the coefficient of determination (R Square) is 0.095 or equal to 9.5%. This figure means that the variable Understanding of the Book of Minhajus Salikin (X) affects the variable Quality of Student Prayer (Y) by 9.5%. While the rest (100% - 9.5% = 90.5%) is influenced by other variables outside this regression equation or variables not examined. Although the effect is low, understanding the book of Minhajus Salikin still contributes to improving the quality of student prayer.Keywords: minhajus salikin, quality of prayer, fiqh, education